A practical example of a software factory: building a custom application for analysing EU Cyber Physical System (CPS) projects using Open Source software components. Issue 1 (13th September 2016) - Palmer, P. J.; Sinclair, M. A.; Siemieniuch, C. E.; De Henshaw, M. J.
Abstract: This paper is a retrospective analysis describing the development of a custom tool to organise data snippets derived from a substantial body of information, and a summary of the insights that this means of analysis provided in a very short time scale. The creation of data driven visualisations are of particular interest as they uncovered more cross‐domain aspects of Cyber‐Physical Systems projects than expert opinion had anticipated. These findings will be discussed fully in a second paper. The focus here is the development of the "Vulture" data scavenging tool using Open Source software as system components to create a custom application to serve the data collection and analysis requirements of a REA (Rapid Evidence Assessment) work‐package within an EU funded project, Road2CPS.